Extending Battery Life using Boost Converter through Feedback Control - Shetty, Prashanth Kumar; Bhat, Somashekhara (International Journal of Engineering and Technology, 2018)
Battery life is an important factor in any portable device. All possible efforts are being made to prolong the usage time of a battery. Eventually when a battery has low charge, the output voltage deteriorates and eventually reaches a point which is not enough to drive the load. This paper proposes a way of boosting the output voltage in this situation to increase the life of a battery before next charge phase, thereby using energy from the battery which would otherwise be unused. The proposed technique uses a DC-DC Boost Converter in Continuous Conduction Mode. An error amplifier with a Type-3 Compensation circuit is used in the feedback path to stabilize the system. The PWM comparator circuit is used to generate the required PWM input signals for the Boost Converter with required Duty Cycle.